2016
DOI: 10.1002/adsc.201501177
|View full text |Cite
|
Sign up to set email alerts
|

One for Many: A Universal Reagent for Acylation Processes

Abstract: This work describes acylation reactions facilitated by at ype of heterocycle-based acyl transfer agent, 2-acyloxypyridazinone.R eactions of 2-acyloxypyridazinone with carboxylic acids yield mixed carbonic anhydride intermediates,w hich are reactive and couldb ec oupled with aw ide range of substrates including acids,a mines,a lcohols,a nd thiols.T he wide substrate scope,e ase of operation (no additive or catalyst), storage and handling stability,a nd atom-efficiency from recycling the heterocycle carrierm ake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The method used for their product ptseparation is column chromatography and the product formation is necessarily temperature-dependent. An extremely specific reagent ethyl-4,5-dichloro-6-oxopyridazine-1-(6H)carboxylate is convenient for conversion of mixed esters, thioesters, amides, and carbonic anhydride from a carboxylic acid [29]. It has been reported that 2-ethoxy carbonyl DCPN are good leaving group [30], stable, atom-economic acyl sources, and non-hygroscopic [31] in the reaction by carboxylic acids [32].…”
Section: Introductionmentioning
confidence: 99%
“…The method used for their product ptseparation is column chromatography and the product formation is necessarily temperature-dependent. An extremely specific reagent ethyl-4,5-dichloro-6-oxopyridazine-1-(6H)carboxylate is convenient for conversion of mixed esters, thioesters, amides, and carbonic anhydride from a carboxylic acid [29]. It has been reported that 2-ethoxy carbonyl DCPN are good leaving group [30], stable, atom-economic acyl sources, and non-hygroscopic [31] in the reaction by carboxylic acids [32].…”
Section: Introductionmentioning
confidence: 99%
“…The starting materials were prepared according to the literature procedures [ 21 , 23 , 30 – 31 ]. The known compounds, 1a , 1b [ 32 ], 1c [ 33 ], 1f–1h [ 34 ], 1i [ 35 ], 1k [ 36 ], 1l [ 31 ], 1m [ 37 ] and 1n [ 38 ] were characterized by comparison of the spectral data with those reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Aromatic ketones are valuable precursors for the synthesis of agrochemicals, pharmaceuticals, fragrances and also dyes. These molecules are generally synthesized by Friedel-Crafts acylation using Lewis acids as catalysts [31][32][33][34][35][36]. However, the need for the excess use of the catalyst, the unfeasible recovery process and the environmental problems have directed researchers to alternative methods.…”
Section: Reactions Catalysed By Lewis Acid Type Dessmentioning
confidence: 99%